Metabolic reprogramming of macrophages during infections and cancer. (28th June 2019) - Wang, Shiyao; Liu, Ruichen; Yu, Qing; Dong, Lin; Bi, Yujing; Liu, Guangwei
Abstract: In response to different microenvironmental stimuli, macrophages are polarized into two populations, M1 macrophages which are classically activated by interferon (IFN)-γ with lipopolysaccharides (LPSs) and M2 macrophages which are alternatively activated by interleukin-4 (IL-4), to perform specific roles in innate immune responses. Accordingly, macrophages occupy distinct metabolic profiles, regulated by orchestrated factors and signaling pathways, including the PI3K-AKT, HIF, c-Myc, AMPK, and PPARs pathways. These factors and pathways play pivotal roles not only in metabolic regulation but also in macrophage polarization. After activation, classically activated M1 macrophages and alternatively activated M2 macrophages display distinct patterns in glucose, lipid, amino acid and iron metabolism. Here, we summarized recently discovered metabolism-related inflammatory signaling factors, along with reprogrammed metabolism, after the activation of macrophages under conditions related to immunity and cancer. Additionally, macrophage regulatory roles in infectious diseases, cancer progression and anti-cancer immunotherapy are discussed in terms of metabolic profiles, providing insight into the prevention and treatment of immune-associated diseases. Highlights: Recent studies about macrophages metabolism in inflammations. Recent studies about macrophages metabolism in cancer progression. Recent study progresses about macrophages metabolism in anti-cancer immunotherapy. Research prospect about macrophage metabolism profile in inflammation.